2006
DOI: 10.1542/peds.2006-1008
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians' Knowledge, Attitudes, and Practices Related to Newborn Hearing Screening

Abstract: Pediatricians and other primary care providers recognize the benefits of early detection and intervention for permanent hearing loss in infants. The current system of newborn hearing screening can be enhanced by strengthening the medical community's involvement in the process from screening to follow-up. Physician roles will be supported through the provision of action-oriented resources that educate parents about the importance of follow-up and that prepare professionals to incorporate appropriate surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
1
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 24 publications
8
102
1
12
Order By: Relevance
“…These are fundamental in a program whose global goal is taking care of hearing [43]. An essential part of this attention is the support given by the primary health care pediatrician [8,29,52]. In the periodic newborn controls, this professional verifies the performance of screening tests, plans follow-up for children with risk factors and evaluates the appropriate diagnostic and therapeutic attention in hearing loss, whether confirmed or still to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…These are fundamental in a program whose global goal is taking care of hearing [43]. An essential part of this attention is the support given by the primary health care pediatrician [8,29,52]. In the periodic newborn controls, this professional verifies the performance of screening tests, plans follow-up for children with risk factors and evaluates the appropriate diagnostic and therapeutic attention in hearing loss, whether confirmed or still to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Many UNHSI programs have been working to educate other stakeholders, but at least the following challenges remain.…”
Section: Lack Of Provider Knowledgementioning
confidence: 99%
“…Consequently, many pediatricians have not yet integrated follow-up on screening results into their newborn-care protocol. 15 One-third of the UNHSI programs reported that pediatricians in their state did not routinely review screening results for their newborn patients (as reported elsewhere in this supplemental issue, 16 this is sometimes because UNHSI programs do not report the needed information to the pediatrician). One-third of the UNHSI programs reported that pediatricians' and audiologists' lack of knowledge about the availability of EI services was a major problem in their state.…”
Section: Many Providers Lack Knowledge Of Ei or Family-to-family Suppmentioning
confidence: 99%
“…Less recognized is the potential benefit of genetic and ophthalmologic evaluation of children and infants with sensorineural hearing loss. 17 Especially in young infants and children, referral to an otolaryngologist for a complete diagnostic assessment is essential. More than 90% of the children with permanent hearing loss are born to "hearing" parents, resulting in a sense of urgency for parents of newly identified children with hearing loss to seek out answers regarding etiology, risk of progression, implications, and other questions.…”
Section: Follow-up and Diagnostic Testingmentioning
confidence: 99%